Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

CookieMonster101

  • 3 years ago

What is the answer to: m( m + 3) + 5m = 3 + m (m - 4)

  • This Question is Closed
  1. CookieMonster101
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    I got m= 3/12

  2. ReconRon
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    \[m^2+3m+5m=3+m^2-4m\] \[12m=3\] \[m=3/12\] \[m=1/4\]

  3. CookieMonster101
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thanks !

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy